EFEKTIFITAS APLIKASI PENJASPEDIA SEBAGAI PENGENALAN OLAHRAGA BERBASIS WEB ANDROID PADA MASA COVID-19 DI SMP N 6 PEKANBARU - Laiya, Edi Sutomo; Wijayanti, Ni Putu Nita; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Corona Virus Disease 2019 (Covid-19) or the Corona virus has changed the order of people's lives in the world, including Indonesia. Education is one of the sectors that makes changes to face-to-face data systems bold. This research was carried out at SMPN 6 Pekanbaru in class VII students, amounting to 435 students who became the population. The sampling in this study used a purposive sampling technique with a certain balance which revealed 220 students who were the sample. This type of qualitative descriptive research uses a survey method with a questionnaire in the form of a questionnaire conducted online. Data analysis using SPSS 25 statistical assistance by testing the validity of Rcount> from Rtable (423) was declared valid, and the results of the 8 statement items were declared valid. Furthermore, the reliability test where RAlpah> 0.600 is declared reliable, then from the 8 items the statement gets a reliable result of 0.896, and the usability test which is to determine the level of effectiveness of the Pennjaspedia application then categorized using the usability level obtained from the overall percentage of respondents' answers of 56 ,8% "very good" so that this physical education application can be used continuously as a physical education learning medium for seventh grade students at SMPN 6 Pekanbaru. Based on the results of the Penjaspedia application with the title "Very Good" concluded that the use of smartphone media during the Covid-19 period in supporting the physical education learning process at SMPN 6 Pekanbaru was very effective and efficient.Key Words: Covid-19 Pandemic, Physical Education, Effectiveness of the PenjaspediaApplication